ANALISIS KUALITAS PELAYANAN PAJAK KENDARAAN BERMOTOR (PKB) DI KANTOR SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) PALU - Suhaeril, Suhaeril (Katalogis, 2015)
This research aims at finding out the quality of good service and finding out the factors that determine the service quality at the ORS office of Palu as a vehicle tax service provider in Palu. The researcher uses a qualitative research method, where data and information are collected using the work matrix instrument and interviews with selected informants. The results shows that the speed and discipline were still in the category of less quickly, the service is late within 60 minutes (1 hour). The service punctuality at ORS office is still in the category of time inconsistent and it is not in accordance with the set condition which is seven (7) minutes to 15 minutes, from the hospitality and decorum, Officers’ service is categorized as good, but in terms of appearance, the officers’ clothing or uniform has not been in accordance with the rules set by the ORS center. And in terms of environmental comfort, the facilities and infrastructure are already adequate but the number and size/volume are inappropriate and they do not follow the established rules. In supporting the service quality at the ORS office of Palu, it is determined by several factors, including organizational structure which shows good condition although it involves three institutions, but each organization is responsible, coordinate integratedly, considering the working relationship with each other is very closely related. Of the factor of capability of officers at ORS office of Palu, if it is judged by the oficers’ education level, it is good, but the number of employees of each element is not in accordance with established rules. In the service system factor at ORS office of Palu, it is exist and already in accordance with the regulations set, but the implementation on the field has not run well.